2021
DOI: 10.1097/eja.0000000000001476
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference and intra-operative tidal volume

Abstract: for the LAS VEGAS study investigators, the PROVE Network and the Clinical Trial Network of the European Society of Anaesthesiology BACKGROUND One key element of lung-protective ventilation is the use of a low tidal volume (V T ). A sex difference in use of low tidal volume ventilation (LTVV) has been described in critically ill ICU patients.OBJECTIVES The aim of this study was to determine whether a sex difference in use of LTVV also exists in operating room patients, and if present what factors drive this dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The findings of the mediation analysis are in line with findings of the previous studies in patients in the ICU ( 16) and in the operating room (12). In contrary to previous findings, we see that differences are only partly explained by sex per se.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings of the mediation analysis are in line with findings of the previous studies in patients in the ICU ( 16) and in the operating room (12). In contrary to previous findings, we see that differences are only partly explained by sex per se.…”
Section: Discussionsupporting
confidence: 90%
“…Differences between females and males with regard to the use of LTVV have been described in surgery patients during general anesthesia (7)(8)(9)(10)(11)(12) as well as critically ill patients in the ICU-and irrespective of the presence of ARDS (13)(14)(15)(16)44). It is uncertain if the sex difference in the use of LTVV also exists in patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…The use of IBW to calculate lung-protective ventilation (LPV) starting tidal volumes ( V t ) for ventilation raises additional considerations. The findings reported in the LAS VEGAS re-analysis by Nijbroek et al 11 point clearly to a phenomenon of systematic overventilation of patients in general, and women in particular. The V t analysis in this study found clustering, and incremental adjustment around default values.…”
Section: The Use Of Ideal Body Weight To Calculate Tidal Volumementioning
confidence: 83%
“…The Oh et al 9 and Nijbroek et al 11 studies share a desire to ensure that patients receive care tailored to their specific needs in a real-world clinical setting. In our analyses, we find that BMI-based IBW estimation, although slightly more arithmetically complex, may be beneficial in both contexts.…”
Section: Discussionmentioning
confidence: 99%
“…De Silva and coworkers evidenced that pacemakers, cardioverter defibrillators, and resynchronization therapy are less used in women than in men, independent of age or comorbidities [95]. In addition, women receive less invasive mechanical ventilation in comparison to men [96], as observed during general anesthesia [97] in critically ill patients [98,99], as well as less dialysis [100]. Furthermore, a German study highlighted that the prevalence of the continuous use of blood glucose monitors depends on age, sex, and gender [101].…”
Section: Access To Mdsmentioning
confidence: 99%